BEHAVIOR OF LACTATION COWS AT LOOSE-BOX-TYPE KEEPING IN LARGE GROUPS UNDER THE INFLUENCE OF HIGH AIR TEMPERATURES - Zakharenko, M. O.; Khotsenko, A. V.; Vashchenko, P. A.; Shostya, A. M.; Polishchuk, A. A.; Usenko, S. O.; Shaferivsky, B. S. (Scientific Progress & Innovations, 2021)
The article describes the elements of behavior and dairy productivity of Holstein breed cows of foreign selection under the effect of high air temperatures, at loose keeping method in cow barns of frame type made from metal structures of 316 x 38 x 11 m, 250 heads in a section. The cage is designed for the simultaneous keeping of 1,000 lactating cows, and equipped with boxes for having rest, fodder and group drinkers with free access of animals to feed and water. The cows were milked three times using the installation of "Parallel" (De Laval). It has been established that air temperature and technological operations such as feed distribution and milking have influenced the behavior of high-yielding lactation cows. It has been established that the effect of high air temperature of on lactation cows, when kept in metal structures, affects water consumption, the duration of animals’ rest lying and especially standing, worsens feed consumption. The obtained data on the dependence of the air temperature of the cowshed on the outside conditions can be explained by the free air exchange between the indoor and outdoor environment, which is carried out through the side screens and gates. This is confirmed by the indicator of relative humidity, the value of which also depended on the parameters of the outside air. It was found that the relative humidity in the first cowshed from 9 to 18 o'clock in the evening decreased from 78.3 to 53.3 % as well as outside air humidity where its value also varied from 71.3 to 51.3 %. A similar pattern was found for the relative air humidity in the second cowshed, the value of which in the specified period decreased from 69.3 to 56.3 %. The speed of air movement, which was within the norm in both cowsheds, depended the least on the influence of external factors. Therefore, on the basis of the conducted researches it is possible to draw the conclusion about the dependence of air temperature and humidity mode in cowsheds of frame type from metal structures on parameters of external air. The data obtained must be taken into account at high temperatures of both outdoor and indoor air, which adversely affects the behavior, physiological processes and milk productivity of cows.